HARMONIZATION OF STUDENTS' PHYSICAL FITNESS USING THE GROUP METHOD - Borisevich, S.A.; Treshcheva, O.L.; Karpeev, A.G.; Koksharov, A.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to search, test and implement methods of organizing the educational process that contribute to the harmonization of the physical fitness of male students. Results and conclusions. The article concretizes the concepts of harmonious physical readiness of students and lagging behind physical qualities. Based on the results of the study, model characteristics of the development of the main physical qualities of modern students were determined, a classification of male students was developed according to the level and harmony of physical fitness. A technology for determining the lagging indicators of the development of physical qualities of students is proposed. The article substantiates the expediency of using blocks of physical exercises for the development of lagging physical qualities. An effective form of organizing the implementation of these exercises is a group method using temporary typical subgroups. Subgroups are formed according to the results of testing and include students with lagging indicators of the physical quality developed in this part of the lesson. As a result of the experiment, the effectiveness of this technique was proved. By the end of the experiment, the number of students with harmonious physical fitness increased significantly.